Prognozing of hyperplastic disoders in postmenopause women - S E Arakelov; A M Gasparyan; I M Ordiyantc (RUDN Journal of Medicine, 2008)
The investigation is devoted to studying of genetic aspects in hyperplastic disorders in postmenopause women due to allele distribution of GPIIIα gene, that controls the synthesis of integrines, lysosomal activity of enzymes, the production of embryo-antibodies. Basing on the comparison of the results of genetic investigation with the condition of immune-system and the level of the activity of lyzosomal enzymes, we tried to open the mechanism of appearing and development of hyperplastic disorders in postmenopause. New criteries have been offered for prognosing and prophylaxis of hyperplastic disoders in postmenopause.